Component analysis of cultivated ginseng and mountain ginseng to the change of ginsenoside components in the process of heating and fermentation - Bae -Cheon Cha; Hye -Chul Yoon; Dae-Ho Lee; Jae-Seuk Park; Ki-Rok Kwon (Korean Pharmacopuncture Institute, 2010)
Objectives: The aim of this experiment is to provide an objective differentiation of cultivated ginseng, mountain ginseng through component analysis, and to know the change of ginsenoside components in the process of heating and fermentation. Methods: Comparative analyses of ginsenoside Rb1, Rb2, Rc, Rd, Re, Rf, Rg1, Rg3, Rh1 and Rh2 from the cultivated ginseng 4 and 6 years, and mountain cultivated ginseng were conducted using HPLC (High Performance Liquid Chromatography, hereafter HPLC). And the same analyses were conducted in the process of heating and fermentation using mixed Lactobacillus rhamnosus, Lactobacillus plantarum, Bifidobacterium lactis for 7 days. Results: The change of ginsenosides to the process of red ginseng and fermentation, cultivated ginseng and mountain cultivated ginseng were showed another results. Mountain ginseng showed a lot of change compared with cultivated ginsengs. In the 7 days of fermentation, mountain ginseng showed that ginsenoside Rg1, Rb1, Rb2, Rc, and Rd were decreased and increased ginsenoside Re, Rf, Rg3 and Rh1 were increased compared with cultivated ginseng. Conclusions: It seemed that ginsenosides of mountain cultivated ginseng was better resolved than cultivated ginseng because the difference of structure or distribution of ginsenosides in the condition of fermentation.